A structural homologue of the plant receptor D14 mediates responses to strigolactones in the fungal phytopathogen Cryphonectria parasitica. Issue 3 (26th February 2022) - Fiorilli, Valentina; Forgia, Marco; de Saint Germain, Alexandre; D'Arrigo, Giulia; Cornu, David; Le Bris, Philippe; Al‐Babili, Salim; Cardinale, Francesca; Prandi, Cristina; Spyrakis, Francesca; Boyer, François‐Didier; Turina, Massimo; et al.
Summary: Strigolactones (SLs) are plant hormones and important signalling molecules required to promote arbuscular mycorrhizal (AM) symbiosis. While in plants an α/β‐hydrolase, DWARF14 (D14), was shown to act as a receptor that binds and cleaves SLs, the fungal receptor for SLs is unknown. Since AM fungi are currently not genetically tractable, in this study,  we used the fungal pathogen  Cryphonectria parasitica,  for which gene deletion protocols exist, as a model, as we have previously shown that it responds to SLs. By means of computational, biochemical and genetic analyses, we identified a D14 structural homologue, CpD14. Molecular homology modelling and docking support the prediction that CpD14 interacts with and hydrolyses SLs. The recombinant CpD14 protein shows α/β hydrolytic activity  in vitro  against the SLs synthetic analogue GR24; its enzymatic activity requires an intact Ser/His/Asp catalytic triad. CpD14 expression in the  d14‐1  loss‐of‐function  Arabidopsis thaliana  line did not rescue the plant mutant phenotype. However, gene inactivation by knockout homologous recombination reduced fungal sensitivity to SLs. These results indicate that CpD14 is involved in SLs responses in  C. parasitica  and strengthen the role of SLs as multifunctional molecules acting in plant–microbe interactions.